EVOLUÇÃO DO USO DA TERRA NA BACIA DO RIO LAVAPÉS (BOTUCATU, SP) POR UM PERÍODO DE 27 ANOS - Campos, Sérgio [UNESP]; Cardoso, Lincoln Gehring [UNESP]; Barros, Zacarias Xavier De [UNESP]; Araújo, Armindo Alves De [UNESP]; Ribeiro, Fernanda Leite [UNESP]; Castro, Tarcísio Mauro R. De [UNESP] (Departamento de Engenharia Agrícola - UFCG, 1998)
The present study aimed at evaluating the evolution of land use in the Lavapés river basin, Botucatu, São Paulo State, over a twenty-seven period, considering fíve kinds of vegetative covers (forest land, savanna rangeland coffee cropland, sugar cane and reforestation). The study was based on the vertical aerial photographs from 1962, in approximately 1:25.000 nominal scale, and on the LANDSAT-5 Multispectral Scanner 1989 images, in 1:50.000 scale. The analysis of the results revealed that sugar cane was the only vegetative cover that had an area expansion, which was due to reduction in coffee cropland, forestland, reforestation and savanna rangeland, refleting the high economic return in the establishment of governamental programs for Proalcohol. The savanna rangeland and coffee cropland showed more reductions in areas than the others. It was observed that, in general, forestland occurred mostly in the higher parts of the sloping area, while savanna rangelands, coffee croplands, sugar canes and reforestation occurred mostly in the intermediate parts. In this context, during 1989 the predominating vegetative cover sequence was sugar cane, forestland, reforestation, savanna rangeland and coffee cropland.

O presente trabalho objetivou avaliar a evolução do uso da terra da bacia do Rio Lavapés, Botucatu, SP, no período de 27 anos, considerando-se cinco tipos de cobertura vegetal (mata, cerrado, café, cana-de-açúcar e reflorestamento) e tendo-se como base as fotografias aéreas verticais de 1962, em escala nominal aproximada de 1:25.000 e a imagem de satélite do LANDSAT-5 de 1989, em escala 1:50.000. Os resultados permitiram constatar que a cana-de-açúcar foi a única cobertura vegetal que apresentou expansão de área, sendo este domínio processado notadamente às expensas da redução de áreas com cerrado, mata, café e reflorestamento, refletindo o alto retorno econômico na implantação dos programas governamentais para o Proálcool, no período. O cerrado e o café, dentre as coberturas vegetais que apresentaram redução, foram as mais significativas nesse espaço de tempo; já as áreas com matas ocorreram geralmente nas partes altas do relevo, enquanto as com cerrado, cafezais, canaviais e reflorestamento, se situaram nas partes medianas; neste contexto, as coberturas vegetais foram, em ordem de predominância em 1989, cana-de-açúcar, mata, reflorestamento, cerrado e café.
EVOLUTION OF LAND USE IN THE LAVAPÉS RIVER BASIN BOTUCATU, STATE OF SÃO PAULO, BRAZIL DURING TWENTY-SEVEN YEARS
Keywords: vegetative cover; photointerpretation; soil occupation; cobertura vegetal; fotointerpretação; ocupação do solo